LITERASI MATEMATIS SISWA DITINJAU DARI EFIKASI DIRI: SYSTEMATIC LITERATURE REVIEW - Ahbi Mahdianing Rum; Dadang Juandi (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
The main purpose of this study is to describe the results of students’ mathematical literacy based on self-efficacy. The method used in this study was Systematic Literature Review (SLR). The total sample was 17 articles of students’ mathematical literacy based on self-efficacy. The samples were articles indexed in SINTA, published in 2018 until September 2022 and located in Indonesia. The description in this study will be reviewed based on the journal indexes, year of publication, methods used, study level, sample size, research locations Through the SLR, it was obtained that in the past five years, most of the articles were published in SINTA 4, the most publications of students’ mathematical literacy based on self-efficacy happened in 2022, mix method became the most method used in this study, students’ in junior high school was dominantly used as the sample of this research, many researchers used more than or equal to 30 samples, and its research was widely conducted in Java